Organic Light-Emitting Diode with Color Tunable between Bluish-White Daylight and Orange-White Dusk Hue - Shih-Yun Liao; Sudhir Kumar; Hui-Huan Yu; Chih-Chia An; Ya-Chi Wang; Jhong-Wei Lin; Yung-Lee Wang; Yung-Chun Liu; Chun-Long Wu; Jwo-Huei Jou (International Journal of Photoenergy)
The varying color of sunlight diurnally exhibits an important effect on circadian rhythm of living organisms. The bluish-white daylight that is suitable for work shows a color temperature as high as 9,000 K, while the homey orange-white dusk hue is as low as 2,000 K. We demonstrate in this report the feasibility of using organic light-emitting diode (OLED) technology to fabricate sunlight-style illumination with a very wide color temperature range. The color temperature can be tuned from 2,300 K to 9,300 K, for example, by changing the applied voltage from 3 to 11 V for the device composing red and yellow emitters in the first emissive layer and blue emitter in the second. Unlike the prior arts, the color-temperature span can be made much wider without any additional carrier modulation layer, which should enable a more cost effective fabrication. For example, the color-temperature span is 7,000 K for the above case, while it is 1,700 K upon the incorporation of a nanoscale hole modulation layer in between the two emissive layers. The reason why the present device can effectively regulate the shifting of recombination zone is because the first emissive layer itself possesses an effective hole modulation barrier of 0.2 eV. This also explains why the incorporation of an extra hole modulation layer with a 0.7 eV barrier did not help extend the desirable color-temperature span since excessive holes may be blocked.